Studies on moisture content, storage condition and seed dimension on seed germination: A comprehensive study of the medicinal plant Datura alba Nees. - Pawan Kumar Modi; Dr. Shabnam Bee (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Medicinal plants play a crucial role in treating various common diseases and are often relied upon as essential home remedies in many regions. Datura alba Nees, recognized for its medicinal properties is the necessity for effective seed germination techniques to ensure consistent and enhanced yields. This study aimed to assess the impact of moisture content, storage conditions, and seed dimensions on the germination of Datura alba Nees over 4, 8, 12, 18, and 24 months. The germination percentage of Datura alba Nees seeds gradually decreased with increasing storage time from 4 to 24 months. At a storage temperature of 10°C, 45% of seeds germinated after 4 months, declining to 22.2% thereafter. Conversely, at 40 (±2) °C, the germination rate dropped to 8.9%. Notably, at 10°C, seed germination decreased from 45% to 27.2% over 24 months. Moisture content was sustained for up to 18 months across three storage methods: polythene bags, gunny bags, and cloth bags. Polythene bags maintained maximum moisture for the entire 24-month period, followed by gunny and cloth bags. Furthermore, a positive correlation was observed between seed weight and germination percentage. This study suggests a seed germination methodology to rapidly propagate numerous Datura alba Nees plants, contributing to the conservation and utilization of this medically valuable species.